2015
DOI: 10.18632/oncotarget.3863
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tumor engraftment in patient-derived xenograft models and clinical outcomes in colorectal cancer patients

Abstract: Despite numerous studies involving patient-derived xenograft (PDX) models, few studies have investigated the relationship between the ability of the tumor to engraft (tumorigenicity) and the clinical features of colorectal cancer (CRC). The aim of this study was to determine whether tumorigenicity correlates with clinical outcomes of CRC patients. We included 241 CRC patients who underwent radical surgery from 2010 to 2013. PDX models were established by implanting tumor fragments obtained from these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
7
41
1
Order By: Relevance
“…The engraftment rate of PDX tumors is associated with overall survival (OS), recurrence‐free survival (RFS), disease‐free survival, stage, tumor subtype and other clinical features of the patient. Previous studies have also linked the engraftment rate of PDX tumors to the clinical prognosis of patients . The OS and RFS of donor patients with successful PDX tumor engraftment appear to be significantly shorter than those of donor patients whose tumors fail to generate PDXs.…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The engraftment rate of PDX tumors is associated with overall survival (OS), recurrence‐free survival (RFS), disease‐free survival, stage, tumor subtype and other clinical features of the patient. Previous studies have also linked the engraftment rate of PDX tumors to the clinical prognosis of patients . The OS and RFS of donor patients with successful PDX tumor engraftment appear to be significantly shorter than those of donor patients whose tumors fail to generate PDXs.…”
Section: Clinical Significancementioning
confidence: 99%
“…Additionally, multivariable‐adjusted survival analyses identified tumor engraftment as an independent prognostic marker of poor RFS . Patient tumor samples at a more advanced stage or with more aggressive clinical characteristics showed higher engraftment rates . In a breast cancer study, Kanya et al .…”
Section: Clinical Significancementioning
confidence: 99%
“…2f ). As PDX establishment has been linked to patient outcome, 14 we investigated whether this observation is clinically relevant and can be exploited to stratify patients. We found that low Ki67 gene expression was prognostic for recurrences when analyzing 741 stage II CRC patients (HR = 1.76, p < 0.006; Fig.…”
mentioning
confidence: 99%
“…The results were mixed, with two trials reporting a significant correlation with clinical response and survival [170,171], while the trial using mesothelioma reported no such association [172] Application of the PDX mouse model in regard to clinical outcome has recently been studied in three studies using various, colorectal, and pancreatic cancer tissue. In the studies using pancreatic and colorectal tumor tissue studies a significant correlation between successful tumor engraftment and patient outcome was found, no comparison in regard to drug efficacy was included as primary or secondary study endpoint [173,174] . In a pilot study by Hidalgo et al from 2011, patients were treated according to impact of selected drugs on tumor volume in a PDX mouse model.…”
Section: The Functional Approach: Chemoresponse Assaysmentioning
confidence: 99%